2008
DOI: 10.1111/j.1365-2044.2008.05496.x
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Graves disease thyrotoxicosis and myasthenia gravis: the treatment of the former may dangerously reveal the latter

Abstract: Summary Autoimmune thyroxicosis and myasthenia gravis are often associated. In both diseases, clinical features may include neuromuscular weakness, making their distinction challenging. We report a patient with known Graves disease who presented with generalised fatigue, initially attributed solely to thyrotoxicosis, and who experienced severe respiratory failure linked to associated myasthenia gravis that was unmasked by medication used in the perioperative management of his thyroxicosis. Anaesthetists should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
1
6
0
2
Order By: Relevance
“…While Fang et al [12] recently published an article that showed higher rate of association than our study result. In addition, previous studies also support our result and mentioned the significance relationship between thyroid disorders and myasthenia gravis [9, 13-15]. The association of MG and AITD has been identified in autoimmune polyendocrine syndrome type Il (APS-II), which comprises Addison’s disease, AITD (GD and hypothyroidism caused by chronic lymphocytic thyroiditis), MG, type 1 diabetes, and others [16].…”
Section: Discussionsupporting
confidence: 88%
“…While Fang et al [12] recently published an article that showed higher rate of association than our study result. In addition, previous studies also support our result and mentioned the significance relationship between thyroid disorders and myasthenia gravis [9, 13-15]. The association of MG and AITD has been identified in autoimmune polyendocrine syndrome type Il (APS-II), which comprises Addison’s disease, AITD (GD and hypothyroidism caused by chronic lymphocytic thyroiditis), MG, type 1 diabetes, and others [16].…”
Section: Discussionsupporting
confidence: 88%
“…[4] This association of MG and hyperthyroidism is considered to be due to a common autoimmune mechanism. [6,7] In 75% of patients, symptoms of hyperthyroidism occur before or concurrently with those of MG. Thymic hyperplasia is usually associated with hyperthyroidism. [8] There is a positive relation between the two circulating antibodies against TSH and acetylcholine receptors and they might influence the clinical manifestations of each other.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that pharmacologic management of hyperthyroidism results in the resolution of myasthenia-like symptoms and regression of thymic hyperplasia concomitant with normalization of thyroid functions, [9,4,10] but there can be deterioration also. [7,8,11] This paradoxical phenomenon has been described as a see-saw balance; [11] when myasthenic manifestations increase, thyrotoxic symptoms decrease, and vice-versa. A reverse see-saw relationship has also been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B-blokery, a najbardziej Propranolol zaburzają przewodnictwo nerwowo-mięśniowe i są przeciwskazane u pacjentów z miastenią. Istnieją doniesienia o nasileniu objawów , a także ujawnianiu się miastenii u pacjentów leczonych b-blokerami [60][61][62][63][64][65][66]. Być może również u naszej pacjentki zastosowanie takiego leczenia doprowadziło do nagłego pogorszenia stanu ogólnego i wystąpienia objawów miastenii pod postacią zaburzeń połykania i oddychania.…”
Section: Dyskusjaunclassified